FLUORITE DEPOSITS AT VOZNESENKA IN THE KHANKA MASSIF, RUSSIA: GEOLOGY AND AGE OF MINERALIZATION - Sato K.; Terashima S.; Suzuki K.; Nedachi M.; Ryazantseva M.D.; Vrublevsky A.A.; Khanchuk A.I. (My University, 2003)
A huge fluorite deposit at Voznesenka in the Khanka massif, Far East Russia is concluded to have formed at ca. 450 Ma in Late Ordovician time based on the K-Ar ages for Li-micas in the fluorite ore and greisenized leucogranite within the deposit. This conclusion is inconsistent with the current view of Devonian mineralization that stemmed from widely scattered whole-rock Rb-Sr isotope data for the heterogeneous leucogranite stocks influenced by strong alteration. The Voznesenka and neighboring fluorite deposits may have formed in Cambrian limestone in relation to the intrusion of the Li-F-rich felsic magma which has a similar chemistry to representative Li-F-rich felsic rocks including topaz granite and ongonite or topaz rhyolite; these rocks may be classified as a specific group of highly fractionated felsic magmas.
Keywords: fluorite deposit; Voznesenka; Khanka massif; Russia; Ordovician; Silurian; Permian; Li-F-rich granite; greisen alteration; Cambrian limestone; K-Ar & CHIME ages; Li-mica; zircon; monazite; xenotime; Grodekovo batholith; metallogeny; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Silurian; Палеозой::Ордовикская; Палеозой::Силурийская; Paleozoic::Ordovician